Clinical Practice Guideline for the management of Type 2 Diabetes Mellitus in patients with Heart Failure at Daniel Alcides Carrion National Hospital (Callao, Peru) - Quispe-Pacheco, Measee Carolina (2022)
Objetive: To issue contextualized recommendations for the management of type 2 diabetes mellitus in patients with heart failure. Materials and methods: GPC published in the last 3 years were systematically searched in databases, repositories, and guideline development organizations. Those that achieve a score >60% in the overall evaluation with the AGREE-II instrument were selected. From each guide, the recommendations with their respective clinical question were extracted. The acceptability and applicability of the recommendations to the Peruvian context were evaluated by medical specialists from different institutions in the country (MINSA, EsSalud and armed forces) using the ADAPTE matrix. The final version of the document was approved by a directorial resolution in the “Daniel Alcides Carrión” National Hospital. Results: Of 26 GPC, 3 met the requirements: Diabetes Canada 2018, SIGN 2017 and ESC/EASD 2019. Nine recommendations were adopted. SGLT-2 inhibitors were first choice in treatment, then GLP-1 and DPP4 inhibitors, finally insulin and metformin. Both thiazolidinedions, saxagliptins and sulfonylureas are contraindicated. Conclusions: Through a process of adoption and contextualization, a GPC was developed for the management of type 2 diabetes mellitus in patients with heart failure.